Association between miR‑499 rs3746444 polymorphism and the risk of ischemic stroke A systematic review and meta‑analysis. (2021) - LIU, XIANG‑HONG; LIU, MEI‑LING; LIN, RONG; XING, YA‑PING; ZHAO, TING‑LI; ZHANG, WEN; ZHAO, MING; LIU, QING‑RONG; CAO, KAI
No abstract available